Resection of Bilateral Symmetrical Multiple Level Cervical Ganglioneuroma in a 43-Year-Old Man, a Probable Case of Neurofibromatosis Type-1: Report of a Case and Review of Literature - Seyed Reza Mousavi; Mohammadhadi Amirshahpari Motlagh; Fatemeh Karimi; Bahareh Ebrahimi (Case Reports in Surgery)
Ganglioneuroma is a benign tumor, originating from sympathetic nervous system. Intradural and dumbbell shape spinal ganglioneuroma has been reported in the literature. In this study, we intend to present our case, a 43-year-old man with multiple cutaneous dimples—probably a Neurofibromatosis type-1 (NF-1) case—and subacute myelopathy, who presented with bilateral symmetric dumbbell shape C2/C3 and C4/C5 intradural extramedullary tumors. After resection, the pathologic feature was revealed as ganglioneuroma. We also reviewed the literature for similar cases, which revealed our case to be the 9th bilateral and symmetrical spinal GN, all of which in cervical region; the 5th involving multiple level (the 3rd multiple bilateral symmetrical involvement), the 3rd extending intradurally, and the first case of involving all cervical nerve root ganglions in different sizes. Bilateral symmetrical spinal GNs have also appeared to have different body location, geographic, and gender distribution.